2021
DOI: 10.1111/all.14757
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of treatment response in chronic spontaneous urticaria

Abstract: Chronic spontaneous urticaria (CSU) is defined by the unprompted occurrence of wheals, angioedema or both for more than 6 weeks. 1 Globally, CSU affects 1% of the general population. 2 CSU has an unpredictable course and duration, and many patients suffer for more than 1 year, for example 11%-14% for more than 5 years. 3 CSU patients reportedly have an impaired quality of life with marked impact on interpersonal relationships, work, social functioning and sleep. 4,5 Furthermore, patients with CSU frequently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
82
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 100 publications
1
82
0
3
Order By: Relevance
“…A recent review on the predictors of treatment response in CSU show a strong level of evidence for no association of sex as a possible markers of non-response to OmAb. 23 In their recent work, Yu et al 24 observed that gender is not linked to the speed of achieving complete control with OmAb treatment.…”
Section: Discussionmentioning
confidence: 98%
“…A recent review on the predictors of treatment response in CSU show a strong level of evidence for no association of sex as a possible markers of non-response to OmAb. 23 In their recent work, Yu et al 24 observed that gender is not linked to the speed of achieving complete control with OmAb treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Basophil histamine release assay (BHRA) and basophil activation test (BAT) aid identification of autoimmune CSU (32). It has been reported that positive BHRA results and low levels of total IgE are predictors of a good response to cyclosporine for CSU (33). However, one of the main pharmacodynamic mechanisms responsible for CSU patients' clinical response to omalizumab is to rapidly correct the basopenia in CSU patients and downregulate the expression of FcϵRI on basophils (34).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are potential biomarkers of CSU activity and response to treatment (6). Still, a definitive blood biomarker to predict CSU duration or prognosis is lacking, and anti-thyroid antibodies have been studied for this purpose.…”
Section: Introductionmentioning
confidence: 99%